2022
DOI: 10.1186/s13023-022-02382-x
|View full text |Cite
|
Sign up to set email alerts
|

The health-related quality of life, mental health and mental illnesses of patients with inclusion body myositis (IBM): results of a mixed methods systematic review

Abstract: Background Inclusion body myositis (IBM) is a rare neuromuscular disease (NMD) and effective therapies are not available. Thus, it is relevant to determine the health-related quality of life (HRQoL) in IBM patients including aspects of mental health and illnesses. Objectives To identify and summarize the assessment of HRQoL, mental health and illnesses in IBM, the major factors that determine and influence them as well as the respective influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 62 publications
0
15
0
1
Order By: Relevance
“…The present study has limitations: (i) the patients' diagnoses were self‐reported, therefore prone to measurement bias; (ii) incidence of concomitant fibromyalgia, psychiatry disorders (eg, depression and anxiety) 36 or other factors which may impact pain perception, such as socioeconomic status and level of education; 37,38 (iii) matching of disease duration between different autoimmune diseases as varying elements of damage may influence the pain threshold; (iv) concomitant use of nonsteroidal anti‐inflammatory drugs in several groups and matching; (v) the cross‐sectional nature of this study prevents an evaluation of a causal relationship between the parameters and the potential role of a prospective behavior in many confounding covariables in this study; and (vi) this is a convenience sample prone to selection bias and the number of participants who had access to the e‐survey questionnaire is unknown. Nonetheless, we believe that the multiple comparison groups and the adjustments performed to mitigate the effect of this bias contributed to the validity of our results.…”
Section: Discussionmentioning
confidence: 99%
“…The present study has limitations: (i) the patients' diagnoses were self‐reported, therefore prone to measurement bias; (ii) incidence of concomitant fibromyalgia, psychiatry disorders (eg, depression and anxiety) 36 or other factors which may impact pain perception, such as socioeconomic status and level of education; 37,38 (iii) matching of disease duration between different autoimmune diseases as varying elements of damage may influence the pain threshold; (iv) concomitant use of nonsteroidal anti‐inflammatory drugs in several groups and matching; (v) the cross‐sectional nature of this study prevents an evaluation of a causal relationship between the parameters and the potential role of a prospective behavior in many confounding covariables in this study; and (vi) this is a convenience sample prone to selection bias and the number of participants who had access to the e‐survey questionnaire is unknown. Nonetheless, we believe that the multiple comparison groups and the adjustments performed to mitigate the effect of this bias contributed to the validity of our results.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are relevant for international comparisons using the sparse existing HRQoL and mental health data in IBM patients [41] in order to comprehensively identify or validate procedures as well as therapeutic options to optimize health-care delivery. Therefore, we extensively collected PRO data for subgroup analyses regarding the physical function and severity of dysphagia with the sIFA, SSQ-G and FOIS-G. As to our knowledge, no other study used such PROMs to better understand the HRQoL and mental health in IBM, thus our data could hardly be compared directly regarding physical function and dysphagia to other studies investigated in this research topic [17]. Audag et al identified in their systematic review two studies evaluating dysphagia in IBM patients [42], whereby Olthoff et al [43] detected in 80% dysphagia and impaired Swallowing-Related Quality of Life (SWAL-QoL) compared to reference values and Cox et al [10] found patient-reported dysphagia symptoms in 65%.…”
Section: Discussionmentioning
confidence: 99%
“…According to a sequential mixed-methods design, this quantitative study builds upon a preliminary systematic review about HRQoL and mental health [17], a qualitative interview study about HRQoL and a cost-of-illness (COI) study, in order to better understand the complex care situation of German IBM patients. Therefore, we conducted a cross-sectional survey study in 2021 and recruited IBM patients via the German IBM patient registry www.ibm-registry.org (accessed on 28 July 2023).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations